2022
DOI: 10.3389/fcvm.2021.803744
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in Heart Failure Patients With Preserved Ejection Fraction (GUMPTION Study)

Ziyin Huang,
Xiaofei Mei,
Yufeng Jiang
et al.

Abstract: Introduction: Heart failure with preserved ejection fraction (HFpEF) is associated with disrupted intestinal epithelial function, resulting from intestinal congestion. Intestinal congestion changes the morphology and permeability of the intestinal wall, and it becomes easy for the gut microbiota to change and transfer. Intervention on gut microbiota may become a new target for HFpEF treatment. However, the characteristics of gut microbiota in patients with HFpEF remain unknown. This preliminary report aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 37 publications
2
22
0
2
Order By: Relevance
“…The intestinal microbiota of each case obtained by this study was consistent with previous reports in dogs. Human medicine has reported changes in gut microbiota composition in heart failure patients ( 6 , 7 ). In this study, the FS and LVEF of heart failure dogs were normal and there was no obvious decrease in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal microbiota of each case obtained by this study was consistent with previous reports in dogs. Human medicine has reported changes in gut microbiota composition in heart failure patients ( 6 , 7 ). In this study, the FS and LVEF of heart failure dogs were normal and there was no obvious decrease in cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional and morphological changes in the gut are induced in patients with heart failure, which in turn affects the gut microbiota. In both conditions, heart failure with preserved ejection fraction and heart failure with reduced ejection fraction, there were changes in the gut microbiota ( 6 , 7 ). It has been reported that changes in the gut microbiota and the effects of heart failure on the intestinal tract can lead to systemic inflammation ( 8 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The heart–gut axis might be a novel target for prognosis and treatment in CVDs [ 276 , 277 ]. However, whether the gut hypothesis of heart failure is the cause or the consequence of cardiac damage is unclear [ 278 ]. In this scenario, dietary polyphenols, by modulating the GM and GM metabolites, might positively influence human health [ 279 ].…”
Section: Polyphenol–gut Microbiota Interaction In Cardiovascular Dise...mentioning
confidence: 99%
“…The structure of gut microbiota is also different in patients with different subtypes of HF. Microbial structure of heart failure with preserved ejection fraction (HFpEF) patients was demonstrated to be with an increase of Enterococcus while a decrease of Butyricicoccus in fecal samples ( Huang et al, 2021 ). Meanwhile, studies have also revealed that microbial dysbiosis could induce chronic inflammation and immune dysregulation and ultimately aggravate heart failure with reduced ejection fraction (HFrEF) ( Madan and Mehra, 2020 ).…”
Section: Gut Microbiome Dysbiosis In Heart Failurementioning
confidence: 99%